2016
DOI: 10.1177/0890334416672200
|View full text |Cite
|
Sign up to set email alerts
|

Wide Variability in Caloric Density of Expressed Human Milk Can Lead to Major Underestimation or Overestimation of Nutrient Content

Abstract: The assumption that human milk contains 20 kcal/ounce is no longer supported based on this study. This supports promoting an individualized nutrition strategy as a crucial aspect to optimal nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
0
20
1
Order By: Relevance
“…However, in longitudinal analysis, we found that greater household food insecurity was significantly associated with reduced breast milk intake across this critical period of infant feeding (Table ). The quantities are biologically significant: a 20‐point increase in food insecurity would be associated with infants consuming 79.0 kcal fewer from breast milk (assuming 20 kcal/ounce [Sauer, Boutin, & Kim, ]). Further, a reduction in human milk intake could lead to micronutrient deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…However, in longitudinal analysis, we found that greater household food insecurity was significantly associated with reduced breast milk intake across this critical period of infant feeding (Table ). The quantities are biologically significant: a 20‐point increase in food insecurity would be associated with infants consuming 79.0 kcal fewer from breast milk (assuming 20 kcal/ounce [Sauer, Boutin, & Kim, ]). Further, a reduction in human milk intake could lead to micronutrient deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Other measurable conditions like maternal BMI, age, financial status, and parity may also influence milk macronutrient composition. Sauer (34) observed high variability in macronutrient composition of expressed human milk, even when standardized samples that were not exclusively foremilk or hindmilk were used.…”
Section: Discussionmentioning
confidence: 99%
“…Human milk composition varies considerably within and between mothers and even within a single milk expression. This multidimensional variation in composition is believed to be an adaptation to the infants’ changing needs [ 8 , 9 , 10 ], and geographical region and food supply [ 11 , 12 ]. The variations in human milk composition between individual women and populations have been reported to be in response to cultural differences such as diet and other lifestyle factors [ 13 , 14 ], environmental factors, such as mineral content of the soil that is then reflected in the mineral density of the foods grown there [ 15 ], and human genetic differences [ 16 ].…”
Section: Introductionmentioning
confidence: 99%